1993
DOI: 10.1099/0022-1317-74-8-1715
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and structure of defective interfering RNAs associated with cucumber necrosis virus infections

Abstract: The presence of symptom-attenuating defective interfering (DI) RNAs in a laboratory culture of cucumber necrosis tombusvirus (CNV) was confirmed. Sequencing of eDNA clones of these DI RNAs revealed that CNV DI RNAs retained sequences from the CNV 5"-untranslated and T-terminal regions as well as a portion of the coding region for the 92K protein. Similar sequence arrangements were also observed in symptomattenuating DI RNAs generated de novo from synthetic wild-type CNV transcripts. A comparison of the sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 21 publications
1
36
0
Order By: Relevance
“…n et al, 1991). Similar observations have been made in the related tombusviruses cucumber necrosis virus (CNV ; Finnen & Rochon, 1993) and tomato bushy stunt virus (TBSV ; White & Morris, 1994 a, b).…”
Section: Mutational Analysis Of Defective Interfering (Di)supporting
confidence: 53%
“…n et al, 1991). Similar observations have been made in the related tombusviruses cucumber necrosis virus (CNV ; Finnen & Rochon, 1993) and tomato bushy stunt virus (TBSV ; White & Morris, 1994 a, b).…”
Section: Mutational Analysis Of Defective Interfering (Di)supporting
confidence: 53%
“…In particular, mutant EL4 lacks the AUG start codon of the 33 kDa protein which is retained in nearly all reported tombusvirus DI RNA sequences (Burgy~in et al, 1991;Knorr et al, 1991;Finnen & Rochon, 1993). It was suggested that the presence of this AUG could confer stability to DI RNA molecules by allowing binding to ribosomes (Rochon et al, 1994).…”
Section: Di-21mentioning
confidence: 99%
“…1) (33,(45)(46)(47). These features are also common for DIs derived from other tombusviruses, such as Cymbidium ringspot virus (CymRSV) and Cucumber necrosis virus (CNV) (9,12,13,16,17).Regions I, II, and IV of DIs represent sequences essential for RNA amplification (3,33,45,49), and while region III is dispensable for DI replication of TBSV, it is required for CymRSV DI accumulation (3,17,33). The length of TBSV DI region III varies from 46 to 81 nucleotides (nt), depending on the DI isolate (3,20,47).…”
mentioning
confidence: 99%
“…The tombusvirus coat protein is translated from p41 on subgenomic RNA1 (sgRNA1), and P22 and P19 are expressed from p22 and p19 on sgRNA2 (21)(22)(23)36). TBSV P22 is required for cell-to-cell movement (7,10,42), and P19 is involved in host-specific systemic invasion and symptom development (6,38,41,42) and is active as a suppressor of gene silencing (31,32,44).Tombusviruses can serve as helper viruses for satellite RNAs (1, 2), and they are notorious for the accumulation of defective interfering RNAs (DIs) (13,17,20,24). DIs are spontaneous deletion mutants derived from the helper genome, and they are successfully amplified by trans-acting helper replicase proteins (20, 24).…”
mentioning
confidence: 99%
See 1 more Smart Citation